2019
DOI: 10.1186/s12888-019-2186-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between interpersonal trust and suicidal ideation in older adults: a cross-sectional analysis of 7070 subjects in Shandong, China

Abstract: Backgrounds Suicidal ideation is an important public health issue due to devastating mortality. In the meantime, interpersonal trust was found to be negatively associated with mental disorder and physical health. Although there is increasing evidence that interpersonal trust is a significant predictor of suicidal ideation, evidence of this association is still lacking in the developing world. The aim of this study was to test the association between interpersonal trust and suicidal ideation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
4
8
2
2
Order By: Relevance
“…Elderly participants who were married demonstrated substantial lower psychological pain and suicidal ideation than those divorced, widowed, or never married, in this study, which was in accordance with Yu et al [ 32 ]. Previous studies have supported the effects of high social support and good family relationship on lowering suicidal ideation of older adults [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Elderly participants who were married demonstrated substantial lower psychological pain and suicidal ideation than those divorced, widowed, or never married, in this study, which was in accordance with Yu et al [ 32 ]. Previous studies have supported the effects of high social support and good family relationship on lowering suicidal ideation of older adults [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that elderly participants with poorer individual health (suffered chronic disease, had no fully self-care ability) were more likely to experience psychological pain and suicidal ideation, which was consistent with previous findings [ 31 , 32 , 33 , 35 ]. The elderly with poor health status generally faced more problems regarding their own aging and illness, thus resulting in heavier psychological pressure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, 50 households aged 60 and above were randomly selected in each village (residence). Details of the study design and data collection methods are described elsewhere [24,25]. After preinvestigation and strict sampling, 7088 elderly people were included in the study, and 18 of them were excluded because they had not completed all of the interviews.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%